TRANSFORMATION OF CHARACTER EDUCATION THROUGH DIGITAL TECHNOLOGY-BASED ISLAMIC RELIGIOUS EDUCATION - Muhammmad Aziz; Tatang Aulia Rahman; Azman Ab Rahman (Universitas Islam Depok, 2026)
This study examines innovations in Digital Technology-based Islamic Religious Education (PAI) learning with particular emphasis on Google Classroom as an instrumental vehicle for transforming students' character education. Amid the accelerating digitalization of education in the post-pandemic era, Islamic educational institutions face mounting pressure to respond creatively and adaptively to ongoing transformation without relinquishing their foundational moral and spiritual mission. Grounded in Paulo Freire's critical pedagogy as articulated in Pedagogy of the Oppressed and informed by contemporary principles of digital learning design, this study employs a sequential explanatory mixed-methods approach that integrates a quantitative survey (n = 320) with in-depth qualitative interviews conducted across eight Islamic secondary schools in Java. The study systematically maps the effectiveness of Google Classroom-based Islamic Religious Education in forming students' religious character, digital integrity, and academic responsibility. Findings reveal statistically significant improvements across three key character dimensions: religious character increased by 38.4%, digital integrity by 45.2%, and academic responsibility by 41.7% following one full semester of integrated Digital-PAI model implementation. On the basis of these convergent empirical findings, this study formulates the TAPAK Model (Transformasi Aktif PAI berbasis Karakter / Active Transformation of Character-Based Islamic Education) as a validated implementation framework broadly adoptable by Islamic educational institutions navigating the challenge of meaningful digital transformation.